Inappropriate anti-diuretic hormone (ADH) secretion in association with carcinoma of the bladder. Issue 619 (May 1977) - Kaye, S. B.; Ross, E. J.
Abstract : A case of carcinoma of the bladder complicated by the syndrome of inappropriate anti-diuretic hormone secretion is reported. Management of the syndrome is discussed.